KARAKTERISTIK SIFAT FISIK KAYU JABON(Anthocephalus cadamba Miq) PADA ARAH LONGITUDINAL DAN RADIAL - Ary Widiyanto; Muhammad Siarudin (Jurnal Hutan Tropis, 2016)
This study aims to investigate the characteristics of the physical properties of jabon (Anthocephalus cadambaMiq.) wood and its variations in the stem longitudinaland radial direction. A total of 3samplesof jabontrees were taken from private forest in Talagawangi Village, Pakenjeng sub-District, Garut District, West Java Province. Speciments of physical properties were taken at 3 different heightsof the longitudinal direction(bottom, midle and top of trunk)as well as 3 differentradialdirections (near pith, middle and near bark)of the jabontrunk. The observation focused on the physical properties in three position of both longitudinal and radial orientation. The parameters observed were green wood moisture content(GMC), air-driedmoisture content (ADMC), specific gravity on green wood moisture volume (SGG), and specific gravity on air-dried moisture volume (SGAD). Result showed that the average of GMC and ADMC of jabon wood were 118,43% and 15.36% respectively, while SGG and SGAD are 0.33 and 0.37 respectively.The specific gravity (both SGG and SGAD) of jabon wood was significantly differencein bothlongitudinal and radial direction; while the ADMC and FMC were not significantly difference for longitudinal direction but significantly difference for radial direction. On radial direction, the GMC decreased from the pith to midle and increased near ther bark; while the ADMC regularly decreased from the pith to bark. The specific gravity value on the longitudinaldirection consistently increases from the bottom of the trunk to the top. On radial direction, the specific gravity value consistently increases from the pith to near the bark.Penelitian ini bertujuan untuk mengetahui karakteristik sifat fisik kayu jabon (Anthocepalus cadamba Miq) dan variasinya pada arah longitudinal dan radial batang.Sebanyak 3 pohon, masing-masing diambil sampel 3 titik pada arah longitudinal dan radial batang kayu jabondiambil dari hutan rakyat Desa Talagawangi, Kecamatan Pakenjeng, Kabupaten Garut, Provinsi Jawa Barat.Parameter-parameter sifat fisika kayu yang diukur adalah kadar air segar (KAS), kadar air kering udara (KAKU),  berat jenis pada volume segar (BJS) dan berat jenis pada volume kering udara (BJKU). Hasil penelitian menunjukkan bahwa kayu jabon memiliki KAS rata-rata  118,43%, KAKU  15,36%, BJS 0,33 dan BJKU  0,37.Berat jenis kayu jabon berbeda sangat nyata pada arah longitudinal maupun radial, sedangkan KAS dan KAS berbeda nyata untuk arah arah radial tetapi relatif seragam pada arah longitudinal.  KAS kayu jabon pada arah radial memiliki pola sebaran menurun dari arah dekat empulur ke bagian tengah, kemudian meningkat ke arah sisi; sementara KAKU menurun secara konsisten dari bagian dekat empulur ke bagian dekat kulit. Berat jenis kayu jabon pada arah longitudinal memiliki pola sebaran meningkat secara konsisten dari bagian pangkal ke bagian ujung. Pola sebaran berat jenis pada arah radial meningkat secara konsisten dari bagian dekat empulur ke arah kulit kayu.